2018
DOI: 10.18632/oncotarget.24031
|View full text |Cite
|
Sign up to set email alerts
|

SNP-array lesions in core binding factor acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) with t(8;21) and inv(16), together referred as core binding factor (CBF)-AML, are recognized as unique entities. Both rearrangements share a common pathophysiology, the disruption of the CBF, and a relatively good prognosis. Experiments have demonstrated that CBF rearrangements were insufficient to induce leukemia, implying the existence of cooperating events. To explore these aberrations, we performed single nucleotide polymorphism (SNP)-array in a well-annotated cohort of 198 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Several studies have demonstrated that CCDC26 controls myeloid leukemia cell growth through regulating KIT expression. CCDC26 knockdown upregulated c-KIT mRNA levels [63,64]. Additionally, a study on pancreatic cancer and CDC26 showed that CCDC26 was responsible for the growth and apoptosis of pancreatic cancer cells, partly by regulating PCNA and Bcl2 expression.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have demonstrated that CCDC26 controls myeloid leukemia cell growth through regulating KIT expression. CCDC26 knockdown upregulated c-KIT mRNA levels [63,64]. Additionally, a study on pancreatic cancer and CDC26 showed that CCDC26 was responsible for the growth and apoptosis of pancreatic cancer cells, partly by regulating PCNA and Bcl2 expression.…”
Section: Discussionmentioning
confidence: 96%
“…The prognostic relevance of UPD in CN-AML has not been adequately investigated, although there is evidence that specific UPDs can impact AML patient outcome (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To better define the utility of UPDs for prognostic risk stratification of CN-AML patients, we herein screened a large cohort of adult de novo CN-AML patients for UPDs and investigated their associations with patient survival and relationship with recurrent gene mutations.…”
Section: Cn-aml Patients By Definition Do Not Have Chromosomal Abnormmentioning
confidence: 99%
“…Bone marrow or peripheral blood samples at diagnosis were analyzed by a Cytoscan HD array (ThermoFisher (Santa Clara, CA, USA)) according to the manufacturer's instructions, as previously described [8]. Data were screened according to the Chromosome Analysis Suite (ChAS) 3.1 software (ThermoFisher), with stringent filters.…”
Section: Snp-a Karyotypingmentioning
confidence: 99%